Prospective analysis of the utility of 18‐FDG PET in Merkel cell carcinoma of the skin: A Trans Tasman Radiation Oncology Group Study, TROG 09:03. Issue 3 (5th February 2018) - Poulsen, Michael; Macfarlane, David; Veness, Michael; Estall, Venessa; Hruby, George; Kumar, Mahesh; Pullar, Andrew; Tripcony, Lee; Rischin, Danny
Abstract: Introduction: TROG 09.03 prospectively studied the utility of Fluorine‐18 Fluorodeoxyglucose (18‐FDG) PET in the management of Merkel cell carcinoma of skin. Methods: Following consent and registration, a pre‐treatment FDG‐PET/CT was performed. Sites of avid disease were confirmed by cytology where practicable. Following surgery, patients with AJCCv7 Stages IIA‐IIIB disease were treated with chemo‐radiotherapy and reassessed with a post‐treatment PET. Results: Fifty‐eight subjects (45 males and 13 females, median age 68 years) were enrolled between 2011 and 2015, 43 patients of whom went on to receive chemo‐radiotherapy. An occult primary was present in 22 (37.9%), T1 in 22 (37.9%) and T2 disease in 14 (24.1%). Nodal disease was present in 69% of cases. Fifty per cent of subjects had gross residual disease at the primary site and/or nodal site at the time of registration. 18‐FDG PET/CT had a sensitivity of 94.74% (95% CI 82–99.3%) and a specificity of 88.24% (95% CI 63.56–98.54). The positive predictive value was 94.74% (83.01–98.51) and the negative predictive value was 88.24% (95% CI 65.81–96.69). The pre‐treatment PET influenced a treatment decision in 27.6% of cases. Upstaging occurred in 15 (25.9%), with no down staging. Other diseases were identified in 4 (6.9%) patients. Univariate analysis failed to demonstrate that pre‐treatment SUV levels or a negative post‐treatment PET had any impact on overall survival. PET staged patients had 89% 3‐year in‐field loco‐regional control and 76% 3‐year overall survival. Conclusion: Staging 18‐FDG‐PET significantly influenced treatment decisions in approximately one‐third of cases of MCC and should be considered in the routine pre‐treatment work‐up. Post‐treatment PET was not found to be prognostic. Funding through the Medicare Benefits Schedule needs to be considered for high risk MCC.